Wing geometric morphometric analysis of dwarf honeybee (Apis florea) populations in Thailand - SASITHON SOIPIJIT; PIYAMAS NANORK SOPALADAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Soipijit S, Sopaladawan PN. 2024. Wing geometric morphometric analysis of dwarf honeybee (Apis florea) populations in Thailand. Biodiversitas 25: 3568-3575. The dwarf honeybee, Apis florea Fabricius, 1787, is native to Thailand and distributed throughout the country. It plays a vital role in agriculture and the environment as an excellent pollinator of crops and economic plants in Thailand. Deforestation and insecticide usage have decreased populations of A. florea. There is a need for more information about the diversity of this species in Thailand, particularly its morphological diversity. This study aimed to determine variation among A. florea populations in Thailand based on geometric morphometrics of right forewings. Samples of adult A. florea worker were collected from 81 colonies across Thailand. Forewing shape variation was examined based on 19 landmark coordinates. The results revealed that landmark number 15 had the highest variance, followed by landmark numbers 14 and 16 with the S2=0.00004646, 0.00004436, and 0.00004024, respectively. Principal component analysis (PCA) showed that A. florea populations were distributed as one group, consistent with discriminant and cluster analyses. In addition, multivariate analysis of variance (MANOVA, ?=0.05) was not significantly different among populations. In summary, A. florea in Thailand had less morphological diversity than Apis cerana Fabricius, 1793 and Apis mellifera Linnaeus, 1758. This exciting information provides valuable insight for conserving A. florea in Thailand.